Exploring the possibility of cautious innovation: the impact of perceived paradoxical leadership on innovative work behavior among collegiate teachers - Wen Li; Cheng-Cheng Yang (Cogent Education)
This study is based on the regulatory focus theory to explore how perceived paradoxical leadership influences collegiate teachers’ innovative work behavior. Drawing from a sample of 555 collegiate teachers in Shandong Province, China, the results indicate that perceived paradoxical leadership significantly enhances innovative work behaviors among collegiate teachers. Additionally, paradoxical leadership was found to positively influence both promotion-focused and prevention-focused behaviors, with a promotion focus clearly demonstrating a notable positive effect on innovative work behaviors. Furthermore, this promotion focus partially mediated the relationship between perceived paradoxical leadership and innovative work behaviors. These findings provide theoretical insights for researchers and practical guidance for college administrators who are aiming to foster innovation among collegiate teachers.